Using smartphone for monitoring colorimetric reactions aiming at determining antioxidant activity - PEDROSO, Daniela de Quadros; KNAUL, Luana Estefani; KAPP, Marcelo Nepomoceno; GONÇALVES, Caroline da Costa Silva; BOROSKI, Marcela (Food Science and Technology, 2024)
The use of technology for antioxidant determination in foods has contributed toward enhancing the applicability of this analysis in in vitro assays. The present study sought to evaluate the activity of antioxidants in food products using the following analytical methodologies: analysis of total phenols, flavonoids, ABTS, DPPH, reducing power by potassium ferricyanide, and FRAP, using the smartphone app PhotoMetrix PRO®. These methodologies underwent analytical validation demonstrating linearity at 95% confidence interval, while residues displayed homoscedasticity and random distribution. The values obtained for the limit of detection (LOD) and limit of quantification (LOQ) were below the working range for all methodologies. The correlation coefficients obtained for the curves were above 0.99, except for the FRAP method. For the analysis, the values obtained for relative standard deviation (RSD %) for repeatability and intermediate precision were lower than 5%, except for ABTS and DPPH analysis, which presented values lower than 10%. The PhotoMetrix PRO® app has proven to be efficient for use in the analysis of whole grape juice samples, when compared to UV-VIS spectrophotometer.